Fiddling while Rome burns: Hannah Arendt on the value of plurality and the role of the political theorist. Issue 2 (4th May 2019) - Royer, Christof
ABSTRACT: The value of human plurality has come under threat by, among others, populist movements. To find illumination of our dark times, political thinkers have recently turned to the political thought of Hannah Arendt. Since the concept of human plurality is at the heart of Arendt's oeuvre, Sophie Loidolt's book Phenomenology of Plurality promises to be a timely and important contribution to both the scholarship on Arendt and the moral-political problems of the present. However, while Loidolt's book offers an impressive phenomenological analysis of Arendt's work, it does not entirely succeed in demonstrating the relevance of Loidolt's phenomenological musings for the political, moral and social problems of our age. My criticism, in other words, is not (only) that Loidolt develops a problematic interpretation of Arendt; my point, rather, is that large parts of this interpretation are of limited political relevance; and my more general point is that interpreters who misconstrue – or refuse to take seriously – Arendt's distinction between the philosopher and the political theorist are bound to fail to grasp the nature, the central orientation and, ultimately, the enormous potential of her distinctly political theory.